John Lund, A Study of the Circulation of Ceramics in Cyprus from the 3rd Century BC to the 3rd Century AD - Olson, Brandon R. (Journal of Hellenistic Pottery and Material Culture, 2017)
The present work represents the concluding volume of the National Museum of Denmark’s research program ›Pots, Potters, and Society in Ancient Greece‹. The initiative, generously funded by the Foundation of Consul General Gösta Enbom, resulted in the publication of five volumes, four edited monographs (›Pottery in the Archaeological Record: Greece and Beyond‹, ›Red-figure Pottery in its Ancient Setting‹, ›The Transport Amphorae and Trade of Cyprus‹, and ›The Regional Production of Red-figure Pottery: Greece, Magna Graecia and Etruria‹) and Lund’s ›A Study of the Circulation of Ceramics in Cyprus from the 3rd Century BC to the 3rd Century AD‹. The specialists called on to contribute to this research program have made a number of important contributions to the study of ancient pottery. Lund focuses on the Hellenistic and Roman pottery from Cyprus from the 3rd century BCE to 3rd century CE to, among other things, determine to what degree ancient ceramics are capable of »contributing to our knowledge of the history of ancient Cyprus – economic or otherwise«. The work is the first monograph devoted entirely to the Hellenistic and Roman pottery from the island, but also contributes to a growing trend among scholars of ancient Cyprus to harness a specific class of material culture to shed light on an ancient Cypriot population that had experienced political ruptures and reorganizations following the arrival of the Ptolemies and later the Romans.